2012
DOI: 10.1016/j.stem.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Cloning and Direct Reprogramming: The Long and the Short Path to Stockholm

Abstract: The two winners of the 2012 Nobel Prize in Physiology or Medicine share more than just this honor; they are both also fearless adventurers, in science and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…When the Yamanaka factors were first published, two of the four TFs, Pou5f1 ( Oct4 ) and Sox2 were known to be important for ESCs. In contrast, the role of the other two TFs, Klf4 and Myc , was not well understood [43]. It was quickly shown that Myc was was not essential to reprogramming ( Oct4 , Sox2 , and Klf4 can reprogram alone), but nonetheless enhanced the efficacy of reprogramming [44].…”
Section: Discussionmentioning
confidence: 99%
“…When the Yamanaka factors were first published, two of the four TFs, Pou5f1 ( Oct4 ) and Sox2 were known to be important for ESCs. In contrast, the role of the other two TFs, Klf4 and Myc , was not well understood [43]. It was quickly shown that Myc was was not essential to reprogramming ( Oct4 , Sox2 , and Klf4 can reprogram alone), but nonetheless enhanced the efficacy of reprogramming [44].…”
Section: Discussionmentioning
confidence: 99%
“…The 2012 Nobel Prize in Physiology and Medicine was awarded to Shinya Yamanaka and John Gurdon for their discoveries on reprogramming somatic cells to pluripotency 124 . The seven years since Yamanaka's first demonstration of somatic reprogramming using defined factors 12 have witnessed much progress in understanding this complex process, and the most straightforward experiments have been done.…”
Section: Perspectivementioning
confidence: 99%
“…The aim of this article is to recount the early history of nuclear transfer in Xenopus as a result of which the recent Nobel award was made (Jaenisch, 2012). Further work in Xenopus that has led on from this up to the present time is covered only briefly, and has been reviewed elsewhere Pasque et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%